1957
DOI: 10.1002/hlca.19570400621
|View full text |Cite
|
Sign up to set email alerts
|

Photochemische Reaktionen. 2. Mitteilung. Über gegenseitige Beziehungen und Umwandlungen bei Bestrahlungsprodukten des Santonins

Abstract: Irradiation of santonin in dioxan solution or in alcohol yields a new isomer, lumisantonin, which in turn has been correlated with 3 known compounds: photosantonin, photosantonic acid and isophotosantonic acid lactone. The chemistry of lumisantonin is interpreted in terms of structure b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Under different reaction conditions the two distinct reaction pathways are competitive. It has been reported [19] that in dioxane the reaction would follow path B rather than path A. In contrast, the reaction proceeds along path A in the crystal.…”
Section: The Competitive Reaction Pathway In the Cleavage Of The Càc mentioning
confidence: 88%
See 2 more Smart Citations
“…Under different reaction conditions the two distinct reaction pathways are competitive. It has been reported [19] that in dioxane the reaction would follow path B rather than path A. In contrast, the reaction proceeds along path A in the crystal.…”
Section: The Competitive Reaction Pathway In the Cleavage Of The Càc mentioning
confidence: 88%
“…[16,17] Many experiments were carried out to explore the photoproducts derived from the a-santonin photochemical reaction in different solvents and a remarkable progress in the structural assignments was made. [18,19] However, the intermediates and products involved in the santonincrystal reaction pathway are less characterized. In 1968, Matsuura and co-worker assumed that during the reaction an unstable intermediate is formed which subsequently yields a product through Diels-Alder and [2+2] cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(55) isolated isophotosantonic lactone fl05) from the irradiation of santonin (104) in aqueous acetic acid. In the same year Jeger (Arigoni et al,56) reported the isolation of lumi-santonin (106). In 1958 Barton e^ al.…”
Section: £=R\j 68 53mentioning
confidence: 99%
“…Photochemical rearrangements of cyclohexadlenones Santonin (XXX) was the first cross-conjugated dlenone to be irradiated (28) Plsch and Richards (34) reported that the santonin -+ lumisantonin rearrangement (XXX -* XXXI ) was sensitized by benzophenone and suggested that it was probably the result of excitation to the rr, TT* triplet sLate. This implied that the rearrangement was due to an electron deficient carbon skeleton.…”
mentioning
confidence: 99%